2015
DOI: 10.1186/s12889-015-2188-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and concomitant co-morbidities of type 2 diabetes mellitus in South Western Germany - a retrospective cohort and case control study in claims data of a large statutory health insurance

Abstract: BackgroundType 2 diabetes mellitus (T2DM) has become a world-wide epidemic. This chronic metabolic disease has a major impact on life expectancy and on quality of life. The burden of this disease includes a number of co-morbidities. However, estimates of prevalence, incidence and associated diseases as well as the current temporal development and regional differences are largely missing for South Western Germany.MethodsLifetime diagnosis-based prevalence, incidence and presence of concomitant co-morbidities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 78 publications
6
31
1
7
Order By: Relevance
“…The Framingham General Cardiovascular Risk Score includes age as one of the major risk factors for stroke and CAD (D'Agostino Sr et al, 2008). (Boehme et al, 2015) show a similar pattern for T2D, and the results of this study are in agreement. The calculations applying the discovered aging coefficient to discrete hazard ratio values show a delay in onset incidence for all analyzed LODs.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The Framingham General Cardiovascular Risk Score includes age as one of the major risk factors for stroke and CAD (D'Agostino Sr et al, 2008). (Boehme et al, 2015) show a similar pattern for T2D, and the results of this study are in agreement. The calculations applying the discovered aging coefficient to discrete hazard ratio values show a delay in onset incidence for all analyzed LODs.…”
Section: Discussionsupporting
confidence: 85%
“…Even though in this study each LOD is analyzed independently, in practice, prioritizing certain LODs for pre-ventative therapy could have a significant effect on other conditions not specifically targeted for treatment. For example, T2D is one of the diseases that cause the most co-morbidities, accelerating onset of cardiovascular and other diseases, sometimes by decades (Boehme et al, 2015). For this reason, preventative treatment of T2D could mean improvements in health or delays in the presentation of a range of LODs, either independently of or in addition to treating their specific gene variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population mortality statistics from the US Social Security Actuarial Life Table [59] provided yearly death probability and survivor numbers up to 119 years of age for both men and women. Disease incidence data from the following sources were extensively used for analysis, using the materials referenced in supplementary Chapter S1 in [36]: Alzheimer's disease: [11,[60][61][62]; type 2 diabetes: [63]; coronary artery disease and cerebral stroke: [64]; and cancers: [65,66].…”
Section: Data Sources Programming and Equipmentmentioning
confidence: 99%
“…Nevertheless, even in Western European countries, diabetes has become increasingly prevalent [1]. Studies have indicated an increase in prevalence from 2.39% in 2000 to 5.32% in 2013 in the United Kingdom (UK) [5], from 6.6% in 2007 to 8.6% in 2010 in southwestern Germany [6], and from 2.8% in 1990 to 4.6% in 2010 in Stockholm, Sweden [7]. In high-income countries, approximately 87–91% of diabetes patients have type 2 diabetes mellitus (T2DM) [3, 4], so the increases seen in the prevalence of diabetes are likely to be due to the increase in T2DM [1].…”
Section: Introductionmentioning
confidence: 99%